Connectivity dan Integrity dalam Space Syntax pada Bangunan Sekolah Al-Biruni Cerdas Mulia Bandung - Permata, Dian Duhita; Al-Fitriani, Egalita Nur; Andriana, Febri Ayu; Kurniawan, Anggia Nurfadilah (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2022)
Learning activities not only use a single classroom however classrooms, laboratories, libraries, etc. Therefore, the relationship between spaces in the school building needs to be concern so that communication and interaction between students and teachers can be conducted smoothly. The research tended to verify the connectivity and integrity of space syntax in the Al-Biruni Cerdas Mulia school building located in the Bumi Panyileukan Complex, Bandung, West Java. Two different levels of education degree were conducted in the building by sharing the room facilities. The analysis method used the depthmapX v.055 software to see the connectivity and the calculation of integrity values in the forms of total depth, average depth, and relative asymmetry. Testing the program and calculating the values resulted in 21 effective rooms on the first floor and 11 ineffective rooms on the second floor of the school building. Through the theory of syntax space, the Â problems regarding the spatial arrangement, layout, and circulation in buildings could be resolved, and communication and interaction between students and teachers could be more effective